STRATEGI RRC DALAM DINAMIKA KONFLIK DI LAUT CHINA SELATAN - Ade Priangani; Jeremy Aldi Rezki Hattu (Universitas Jenderal Ahmad Yani, 2020)
South China Sea (SCS) dispute is a matter of seizure or claim of a territory by some countries is indeed a complicated problem. Conflicts involving China with some members of ASEAN have heated up. To improve relations with ASEAN, China through persuasive attitudes and actions. Due to liberalization strategy of China's political economy over SCS especially to ASEAN. The success of ASEAN over the last 50 years has made ASEAN a market share by the major powers that gave birth to a